Implementasi Perlindungan Hak Anak Pengidap Penyakit HIV/AIDS - Fransiska Kristina Siswanto (Perspektif Hukum, 2015)
The assumption underlying this paper is that there are many challenges faced by those who try to fulfill the rights of chlidren, since what stipulated in the regulations are not separated with those implementation. Regulation and implementation are not closed and separated. Society and government are in strategic position in the implementation of fulfill children’s right especially for children living with HIV/AIDS. Protection and fulfillment of childrens’s right are not only the responsibilty of parents., the role of society and government are also needed.